Electric Pulp Tester Response Thresholds Across Electrode Placement Sites in Maxillary and Mandibular Anterior Teeth: A Cross-Sectional Study - Shafqat Ali Shah; Fawad Ali Shah; Laila Gul; Rizwan Ullah Afridi; Ayesha Noor (Journal of Gandhara Medical and Dental Sciences)
OBJECTIVES